A novel phase-locked loop applied on frequency fluctuation of EAST power supply. (December 2020) - Tan, Liang; Fu, Peng; Wu, Yanan; Lu, Jing; Shen, Xianshun; Li, Jun; Tian, Yunxiang
Abstract: The excellent performance of synchronous phase locked technology is the basis of improving the power quality of Experimental Advanced Superconducting Tokamak (EAST) power system. The conventional synchronous reference frame phase-locked loop (SRF-PLL) with low pass filter (LPF) has a poor filter capacity for the 2nd harmonic component as the fundamental frequency fluctuation due to the high-power, high-parameter operation of the EAST. To improve accuracy of the phase estimation, adaptive notch filter (ANF) will be introduced into the LSRF-PLL to reject the disturbance of 2nd harmonic component, which can adaptively track the fluctuation of fundamental frequency with least mean square (LMS) algorithm. A novel composite algorithm of LPF and ANF SRF-PLL (LASRF-PLL) is presented to suppress the disturbance of the frequency fluctuation and harmonic pollution. At the last, the performance of the proposed LASRF-PLL is finally validated by simulation results of MATLAB software.